Peran Pembelajaran dalam Meningkatkan Kualitas Pendidikan - Faiza Shofiyya Eka Putri; Yunita Putri Lestari; Tias Yulianti; Amelia Yuliartha (Prosiding Konferensi Ilmiah Dasar, 2026)
The quality of education is a multidimensional concept shaped by several interrelated factors within the learning process. This study aims to examine the role of learning in improving the quality of education through four main aspects: the teacher's role as facilitator and motivator, active and innovative learning strategies, the integration of educational technology, and the implementation of Project Based Learning (PjBL). This research employed a literature study method with a qualitative descriptive approach, carried out through the stages of reading, comprehending, recording, and categorizing information from relevant journals. The findings show that teachers play an important role as facilitators who provide a conducive learning environment and as motivators who foster students' enthusiasm for learning. Active and innovative learning strategies, which combine creative methods with technology use, proved effective in enhancing student engagement and 21st-century skills. The integration of technology within the Kurikulum Merdeka also supported more personalized and meaningful learning, while project-based learning strengthened students' critical thinking, creativity, and collaboration skills. Improving the quality of education therefore requires synergy between teacher competence, innovative learning strategies, technological support, and student-centered learning models.